POPULATION PHARMACOKINETICS OF CEFPODOXIME IN BOTTLENOSE DOLPHINS ( TURSIOPS TRUNCATUS ) - Linnehan, Barbara K; Lesman, Steven P; Boucher, Joseph F; Grover, G Scott; Brodie, Erin C; Meegan, Jennifer M; McClain, Abby M; Ross, Kyle P; Jensen, Eric D (Journal of zoo and wildlife medicine, 2024)
Cefpodoxime proxetil is commonly used to treat cetacean patients with suspected or confirmed bacterial infections; however, pharmacokinetic data are needed to guide proper dosing in these species. Cefpodoxime proxetil is a time-dependent, semisynthetic, third-generation cephalosporin, appropriate for once-daily dosing and U.S. Food and Drug Administration-approved for use in dogs with a broad spectrum of activity including gram-positive and gram-negative species. The objective of this study was to evaluate the population pharmacokinetics of cefpodoxime in bottlenose dolphins ( ). A sparse-sampling design was used, with serum from dolphins receiving cefpodoxime proxetil at 10 mg/kg orally every 24 h to treat suspected or confirmed bacterial infections. Serum samples ( = 57) from 24 dolphins were analyzed at 12 time points from 0 to 96 h postdose. Serum samples were analyzed using liquid chromatography-mass spectrometry. Population pharmacokinetic analysis was performed using nonlinear mixed-effects modeling. One- and two-compartment linear models with first order absorption were tested. Covariates including weight, age, and sex were considered for inclusion in the model, and between-subject variability was incorporated. A two-compartment model performed best, where following an oral dose of 10 mg/kg, serum concentration reached a mean maximum concentration of 23.0 µg/ml, mean time to maximum concentration of 5.0 h, and mean half-life of 11.4 h. With daily dosing, accumulation was approximately 18% and steady state was reached by the second dose. Serum protein binding was 82.8% as determined by equilibrium dialysis, similar to plasma protein binding reported in dogs. Based on the population pharmacokinetic model, once-daily oral dosing was systemically absorbed and quickly reached maximum concentrations. The half-life in dolphins appears to be longer than other species studied to date. Given the paucity of antimicrobial pharmacokinetic studies in dolphins, and limited once-daily oral antibiotic options for this species, these data are helpful for clinicians to make informed antimicrobial choices.